Studi Kelayakan Pendirian Pabrik Biodiesel dari CPO melalui Proses Esterifikasi dan Transesterifikasi dengan Kapasitas 6.000 Ton/Tahun menggunakan Alat Utama Reaktor Transesterifikasi - Nieke Dedna; Susy Yuniningsih; Zuhdi Ma’sum (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
Biodiesel is an alternative fuel that can replace conventional diesel and is produced from vegetable oils, one of which is Crude Palm Oil (CPO). The use of biodiesel offers several advantages, including being environmentally friendly, renewable, and producing lower exhaust gas emissions compared to conventional fossil fuels. Therefore, biodiesel has significant potential to reduce dependence on fossil energy and to enhance national energy security. The production process of biodiesel from CPO involves two main reactions, namely esterification and transesterification. The esterification reaction aims to reduce the free fatty acid (FFA) content in the feedstock to prevent interference with the main reaction. Subsequently, the transesterification reaction functions to convert triglycerides into methyl esters as the main biodiesel product, with glycerol as a by-product. This reaction proceeds in the presence of a base catalyst and methanol as the alcohol reactant. The preliminary design of this biodiesel plant is planned with a production capacity of 6,000 tons per year, with the transesterification reactor serving as the main equipment. The reactor is designed to operate at a temperature of 60°C and atmospheric pressure of 1 atm, with a feed capacity of 9,846.417 kg/h. Based on the economic analysis, the plant is considered feasible to be constructed, with a before-tax Return on Investment (ROI) of 86%, an after-tax ROI of 77%, a Pay Out Time (POT) of 1.28 years, a Break Even Point (BEP) of 40.53%, and an Internal Rate of Return (IRR) of 18.60%. Therefore, the establishment of a biodiesel plant using CPO as feedstock in Melawi Regency in 2026 is technically and economically feasible and can contribute to the development of renewable energy in Indonesia